A German Version of the Staff Attitude to Coercion Scale. Development and Empirical Validation - Efkemann, Simone A.; Scholten, Matthé; Bottlender, Ronald; Juckel, Georg; Gather, Jakov (Frontiers in Psychiatry, 2021)
Background: Individual staff factors, such as personality traits and attitudes, are increasingly seen as an important factor in the reduction of coercion in mental health services. At the same time, only a few validated instruments exist to measure those factors and examine their influence on the use of coercion. Aim: The present study aimed to develop and validate a German version of the Staff Attitude to Coercion Scale (SACS). Methods: The original English version of the SACS published was translated into German. Subsequently, it was empirically validated on a sample of N = 209 mental health professionals by conducting an exploratory factor analysis. Results: The three-factor structure in the original version of the SACS, consisting of critical, pragmatic and positive attitudes toward the use of coercion, could not be replicated. Instead, the German version revealed one factor ranging from rejecting to approving the use of coercion. Conclusion: The SACS is one of the first instruments created to assess staff attitudes toward coercion in a validated way. The version of the instrument developed in this study allows for a validated assessment of those attitudes in German. Our results highlight the ethical importance of using validated measurements in studies on the role of staff factors in the reduction of coercion.